Exemption of Agricultural Income From Taxati on Under Income Tax Act- How Far Justi fied? - Bhardwaj , Eshaan (Trinity Law Review, 2024)
The definition of agricultural income is very broad as it includes not only agricultural produce but also various other things defined under Section 2(1A) of the Income Tax Act, 1961. This section defines agricultural income as follows: - Rent or income from agricultural land in India Any rent or income from agricultural land is agri cultural income. Rent or income earned is treated as agricultural income only if land is the direct and actual source and not a secondary or indirect source. • Any income derived from any agricultural activity in the country including processing of agricultural pro duce to make it marketable and sale of such products. Income earned is treated as agricultural if a process is carried out to manufacture a product, which is mar ketable and this process has not changed its original nature.